Knowledge about Aedes mosquitoes, dengue fever and zika virus among primary school students in the dengue cluster areas of Hulu Langat, Selangor - Zul-‘Izzat Ikhwan Zaini,; Norhafizah Karim,; Ismarulyusda Ishak,; Hidayatulfathi Othman,; Wei, Lei Hum (Penerbit Universiti Kebangsaan Malaysia, 2019)
In Malaysia, dengue fever is a common vector-borne disease. Most cases of dengue fever are reported in residential areas. Children are at high risk to be infected because they spend a lot of time around their housing area for outdoor activities. Such areas may have a high number of Aedes mosquitoes. As schools are equipped with infrastructure and medium for effective educational purposes, schools represent the most suitable facilities for learning and teaching process. A crosssectional study was conducted to determine the level of knowledge among students in Hulu Langat on Aedes mosquitoes, dengue fever, and Zika virus. The study also reported on the demographic factors which affected the knowledge level. Based on sample size calculation using G*Power v3.1 software, a total of 171 respondents were needed from the two primary schools involved in the study. Data collection was conducted using a pre-tested questionnaire that consisted of two main sections on demography and knowledge about Aedes mosquitoes, dengue fever and Zika virus. From the total score of 55, the mean knowledge score is 34.2 ± 8.38. Based on the median value of 36.0, about 50.9% of respondents had satisfactory knowledge. From the study, it was found that students from School A, students who had been watching video related to Aedes mosquito, and those with history of dengue infection among family members had a significantly better knowledge score (p < 0.01). In conclusion, knowledge about Aedes mosquitoes and related illnesses need to be enhanced through a comprehensive module and effective educational materials that can serve as a reliable source of i nformation for primary school students.